Patterns of response of breast cancer after neoadjuvant chemotherapy according to molecular subtype - Ghezzawi, Malak; El Charif, Mohamad Hadi; Lteif, Lynn; Panossian, Vahe; Haddad, Anthony; Sarkis, Sali; Zebian, Yara; Kheil, Mira; Maktabi, Mohammad Ali; Fakhruddin, Najla; Abbas, Jaber Al; Assi, Hazem; et al. (Frontiers in Oncology, 2025)
BackgroundNeoadjuvant chemotherapy (NACT) is a key component in the treatment of locally advanced breast cancer, with pathologic complete response (pCR) varying by molecular subtype. This study evaluates pCR rates following NACT in a Lebanese cohort, stratified by molecular and clinicopathological features.Methods: This retrospective cohort included 187 women with stage T1–T4, N1, M0 breast cancer treated at the American University of Beirut Medical Center between 2010 and 2016. Molecular subtypes (Luminal A, Luminal B, HER2-positive, triple-negative) were determined by immunohistochemistry and/or FISH. pCR was defined as ypT0N0. Univariate and multivariate analyses were performed to identify predictors of pCR.Results: The median age was 45 years. Molecular subtype distribution was: Luminal A (28.9%), Luminal B (45.5%), HER2-positive (11.8%), and triple-negative (13.9%). Overall pCR was achieved in 12.8% (24/187) of patients. pCR rates significantly differed across molecular subtypes: HER2-enriched 45.5%, Luminal B 11.8%, triple-negative 11.5%, and Luminal A 1.9% (p = 0.005). Axillary involvement was also significantly associated with pCR (p < 0.001), while clinical T stage, tumor grade, focality/centricity, and chemotherapy regimen showed no significant associations. In multivariable logistic regression, molecular subtype remained an independent predictor of pCR (p = 0.002).ConclusionpCR rates varied markedly among molecular subtypes, being highest in HER2-enriched tumors and lowest in Luminal A. These findings support molecular subtype as a key determinant of treatment response and highlight its role in guiding neoadjuvant treatment strategies.